The bilingual courtroom : court interpreters in the judicial process - Berk-Seligson, Susan (Chicago (Ill.) : University of Chicago press, 1990)
Lit. opg.; reg.
Keywords: Gerechtstolken -- Verenigde Staten; Rechtbanken -- Verenigde Staten -- Vertaaldiensten; Rechterlijke organisatie -- Verenigde Staten